Risk Assessment Criteria Applied to a Screening Exam: Implications for Improving the Efficiency of a Sealant Program - Rachel L. Badovinac, DMD, ScM; Kelly E. Morgan, DMD; Joyce Lefevre, RDH; Sangeeta Wadhawan, BDS, MPH (Blackwell Synergy, 2005)
The present study aimed to determine the ability of first-grade screening exam findings to predict carious lesions in permanent first molars by fourth grade. The ability to identify high-risk children would be useful in the rational allocation of limited public health resources, such as the application of sealants.